2011
DOI: 10.1143/jpsj.80.044705
|View full text |Cite
|
Sign up to set email alerts
|

Mean-Field Study of Charge, Spin, and Orbital Orderings in Triangular-Lattice CompoundsANiO2(A= Na, Li, Ag)

Abstract: We present our theoretical results on the ground states in layered triangular-lattice compounds ANiO2 (A=Na, Li, Ag). To describe the interplay between charge, spin, orbital, and lattice degrees of freedom in these materials, we study a doubly-degenerate Hubbard model with electron-phonon couplings by the Hartree-Fock approximation combined with the adiabatic approximation. In a weakly-correlated region, we find a metallic state accompanied by √ 3 × √ 3 charge ordering. On the other hand, we obtain an insulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Amongst the many possible phases uncovered for a selection of independent interaction strengths in the Hamiltonian were phases of charge ordered type. [15]…”
Section: Modeling Of Charge Order Transitionsmentioning
confidence: 99%
“…Amongst the many possible phases uncovered for a selection of independent interaction strengths in the Hamiltonian were phases of charge ordered type. [15]…”
Section: Modeling Of Charge Order Transitionsmentioning
confidence: 99%
“…Vernay et al 29 , for example, studied the evolution of orbital ordering as a function of t /t in a spinful model via both mean-field and exact diagonalization, but they did not consider the charge ordering induced by the intersite repulsion V . Uchigaito et al 32 performed a mean-field analysis of the effects of both the Hund and Jahn-Teller couplings on the electron ordering as a function of t /t; however, because the repulsion V was not included in the model, no pinball-liquid phase was found at realistic values of the Hubbard repulsion U , which is at odds with the experimental observations in AgNiO 2 . The question has also been addressed from an ab initio point of view 33 , including both local and nonlocal interaction effects, but without providing systematic studies as a function of the microscopic Hamiltonian parameters.…”
Section: A Spinless Two-orbital Extended Hubbard Modelmentioning
confidence: 98%
“…The transfer integrals along the lattice vectors u 1 , u 2 , and u 3 = u 2 − u 1 sketched in Fig. 1 can be expressed in terms of two independent parameters t and t as 27,29,32 :…”
Section: A Spinless Two-orbital Extended Hubbard Modelmentioning
confidence: 99%
“…[ 15 ] It is demonstrated that transition metals (TMs) are attracted to these vacancies due to the deintercalation of Li ions. [ 16 ] To tackle these issues, many attempts have been made, such as surface modification and element doping. In particular, partial substitution of TMs (Ni, [ 17–29 ] Co, [ 17,18,22,24,25,30–33 ] Fe [ 22,28,30,32–38 ] ) has proven that this method can improve the performance of LMOs, such as electrical conductivity and structural stability, effectively.…”
Section: Introductionmentioning
confidence: 99%